Jim Crow, Literature, and the Legacy of Sutton E. Griggs (New southern studies., 2013)
Imperium in Imperio (1899) was the first black novel to countenance openly the possibility of organized black violence against Jim Crow segregation. Its author, a Baptist minister and newspaper editor from Texas, Sutton E. Griggs (1872-1933), would go on to publish four more novels; establish his own publishing company, one of the first secular publishing houses owned and operated by an African American in the United States; and help to found the American Baptist Theological Seminary in Tennessee. Alongside W.E.B. Du Bois and Booker T. Washington, Griggs was a key political and literary voice.